2021
DOI: 10.2337/figshare.14884902
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Profiles of Glucose Metabolism in Different Prediabetes Phenotypes, Classified by Fasting Glycemia, 2-Hour OGTT, Glycated Hemoglobin, and 1-hour OGTT: An IMI DIRECT Study

Abstract: Differences in glucose metabolism among categories of prediabetes have not been systematically investigated. In this longitudinal study, participants (<i>N</i>=2111) underwent 2h-75g OGTT at baseline and 48 months. HbA1c was also measured. We classified participants as having isolated prediabetes defect (impaired fasting glucose, IFG; impaired glucose tolerance, IGT; HbA1c-prediabetes, IA1c), two defects (IFG+IGT, IFG+IA1c, IGT+IA1c), or all defects (IFG+IGT+IA1c). Beta-cell function (BCF) and insu… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(9 citation statements)
references
References 0 publications
0
8
1
Order By: Relevance
“…Apart from PTDM, we evaluated thresholds for increased diabetes risk using ADA criteria for prediabetes , on the basis that IGT 5 as well as IGT and/or IFG pose specific risk factors after transplantation 6 . In the general population, IGT and IFG have also been shown to be characterized by distinct metabolic characteristics 30 . HbA 1c was not added as a reference criterion for prediabetes because, to our knowledge, HbA 1c 5.7%–6.4% (39–47 mmol/mol) has not been linked to cardiovascular events after transplantation 6 and was only evaluated as an index test, in contrast to IGT and IFG.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Apart from PTDM, we evaluated thresholds for increased diabetes risk using ADA criteria for prediabetes , on the basis that IGT 5 as well as IGT and/or IFG pose specific risk factors after transplantation 6 . In the general population, IGT and IFG have also been shown to be characterized by distinct metabolic characteristics 30 . HbA 1c was not added as a reference criterion for prediabetes because, to our knowledge, HbA 1c 5.7%–6.4% (39–47 mmol/mol) has not been linked to cardiovascular events after transplantation 6 and was only evaluated as an index test, in contrast to IGT and IFG.…”
Section: Methodsmentioning
confidence: 99%
“…6 In the general population, IGT and IFG have also been shown to be characterized by distinct metabolic characteristics. 30 HbA 1c was not added as a reference criterion for prediabetes because, to our knowledge, HbA 1c 5.7%-6.4% (39-47 mmol/mol) has not been linked to cardiovascular events after transplantation 6 and was only evaluated as an index test, in contrast to IGT and IFG. The diagnostic accuracy of FPG 100-125 mg/ dl (5.6-6.9 mmol/L) and HbA 1c 5.7%-6.4% (39-47 mmol/mol) 1 were therefore assessed in the absence of PTDM and compared with the OGTT-derived diagnosis of IGT and IGT and/or IFG.…”
Section: Laboratory Measurements and Definitionsmentioning
confidence: 99%
“…Very few previous studies have investigated prediabetes metabolic phenotype and cardiometabolic benefits from long-term lifestyle interventions, but some studies reported differences between individuals with IFG+IGT vs iIFG in type 2 diabetes incidence. In the Innovative Medicines Initiative Diabetes Research on Patient Stratification (IMI DIRECT) study, without intervention, diabetes incidence was higher in individuals with IFG+IGT vs iIFG (30). This pattern, however, did not change after the lifestyle intervention.…”
Section: Discussionmentioning
confidence: 98%
“…Accordingly, in diabetes and CVD prevention, individuals with prediabetic hyperglycemia but normal HbA1c should also be considered a target population and should not be ignored. Moreover, in the IMI DIRECT study, individuals with both prediabetic hyperglycemia and intermediate HbA1c, especially with intermediate HbA1c+IFG+IGT, had more severe impairments of both β-cell function and insulin sensitivity and higher risk of developing diabetes, compared with those with iIFG and iIGT (30). In the Whitehall II Study, whilst Vistisen et al (33) demonstrated that prediabetes phenotypes influenced CVD risk, the risk was primarily explained by the clustering of cardiometabolic risk factors associated with hyperglycemia (e.g.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation